Europe's Fragile Unity. Issue 1 (2nd January 2023) - Poletti, Arlo
Abstract: The EU is unlikely to develop the kinds of efficient collective responses to the Russia–Ukraine war that it produced in reaction to the COVID-19 pandemic. The conditions of strategic interdependence generated by the Ukraine crisis are more demanding than those triggered by the pandemic because its consequences are asymmetrically distributed across member states. Germany will find it difficult to play the role of regional stabiliser, anti-Europe parties could become stronger, new intra-European cleavages may arise over collective goals, and the expansion of the crisis's time horizon could weaken prospects for effective collective action.